Solve for \( z \) \[ \begin{array}{l}3(z-14.9)+-7=0.71 \\ z=\square \\ \text { Submit }\end{array} \]
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
Let's solve for \( z \) step by step. Starting with the equation: \[ 3(z - 14.9) - 7 = 0.71 \] First, we will simplify the equation. Distributing the 3 gives us: \[ 3z - 44.7 - 7 = 0.71 \] Combining like terms leads to: \[ 3z - 51.7 = 0.71 \] Next, we isolate \( 3z \) by adding 51.7 to both sides: \[ 3z = 0.71 + 51.7 \] Calculating the right side: \[ 3z = 52.41 \] Now, divide both sides by 3 to solve for \( z \): \[ z = \frac{52.41}{3} \] Calculating this gives: \[ z = 17.47 \] So, the solution is: \[ z = 17.47 \]